Numerical methods in multidimensional radiative transfer - Kanschat, Guido; Meinköhn, Erik; Rannacher, Rolf; Wehrse, Rainer (SpringerLink Bücher, 2009)
Introduction: The Radiation Field and its Transfer Equation -- Stochastic Properties of the Radiative Transfer Equation -- An Approach to Neutrino Radiative Transfer in Supernova Simulations -- A Finite Element Method for the Even-Parity Radiative Transfer Equation Using the P N Approximation -- Solution of Radiative Transfer Problems with Finite Elements -- A General-Purpose Finite Element Method for 3D Radiative Transfer Problems -- Radiative Transfer in 4D: The Inclusion of Kinematical Information -- A Problem-Orientable Numerical Algorithm for Modeling Multi-Dimensional Radiative MHD Flows in Astrophysics – the Hierarchical Solution Scenario -- Rapidly-Converging Methods for Solving Multilevel Transfer Problems -- Radiative Transfer in NLTE Model Atmospheres -- The Solution of the Radiative Transfer Equation in Axial Symmetry -- Multidimensional Radiation Hydrodynamics -- Probing the Initial Conditions for Star Formation with Monte Carlo Radiative Transfer Simulations -- Radiative Transfer Through the Intergalactic Medium -- Radiative Transfer with Finite Elements: Application to the Ly? Emission of High-Redshift Galaxies -- Radiative Transfer Problem in Dusty Galaxies: Ray-Tracing Approach -- Shape Reconstruction for an Inverse Radiative Transfer Problem Arising in Medical Imaging.